Mobile Application Design For Startup Zyon Using The Design Thinking Method - Ajeng Yunita; Tiara Verita Yastica; Budi Praptono (International Journal of Innovation in Enterprise System, 2023)
Zyon is one of the startups in the mental health field that concern of inadequate handling of mental health issues. Consequently, the design of the Zyon application is driven by the aim of addressing these challenges and providing user-oriented solutions. This research focuses on the integration of users and psychologists on a platform, using the design process that incorporates the five stages of design thinking: empathize, define, ideate, prototype, and test. Through in-depth interviews, observations, and expert validation, a conceptual framework for the Zyon application was formulated, resulting in the creation of application mockups. The Zyon application offers consultation services and a range of features to enhance the interaction between users and psychologists, ultimately aligning with user needs. The application design, validated by respondents using the System Usability Scale (SUS) with a score of 87.75, signifies its high usability and fulfillment of acceptable requirements. This research contributes to the advancement of mental health services by delivering an effective and user-friendly application that caters to the needs of its users and psychologists.